Novel electrochemical biosensor key significance of smart intelligence (IoMT & IoHT) of COVID-19 virus control management. (November 2022) - Paladhi, Amogha G.; Manohar, M.; Pal, Kaushik; Vallinayagam, Sugumari; Packirisamy, Azhagu Saravana Babu; Bashreer, Vajiha Aafrin; Sai Nandhini, R.; Ukhurebor, Kingsley Eghonghon
Abstract: Recent outbreak of COVID-19 pandemic has led to the different possibilities of the development of treatment against corona virus. To know the phylogenicity of SARS-CoV, various studies have been conducted with the outcome of the results showing virulence is caused due to spike protein. Various detection techniques with clinical approach like imaging technology, RT-PCR etc. are comparatively expensively than the use of biosensors. Nano-biosensors have an excellent way of approach to track the conditions of individual and public providing information about the existing condition and treatment status. Electrochemical nano-biosensors are referred as an excellent way of detection. The use of graphene based electrochemical nano-biosensors are most advantageous due to its elevated properties. Fluorescence investigation is one of the precise ways of sensing, optical biosignals that helps in obtaining real time results with high accuracy and negligible changes. The potential application of nano-biosensors are very wide, improvised and advanced Nanotechnology helps in the use of nano-biosensors detect all possible biosignals. Significant ubiquitous IoT-enabled novel sensor technologies that can be potentially utilized to respond various facets the growing COVID-19 pandemic from diagnostic and therapeutics to the prevention stage. Highlights: Various electrochemical biosensors utilization for the detection of SARS-CoV-2/COVID. Accurate detection of COVID compared to the conventional RT-PCR, ELISA methods. Explored viral antigen detection, antibody detection and IoT, IoHT, IoMT biosensors.